EVALUATION OF DIFFERENT SOIL EXTRACTANTS FOR ASSESSING BORON SUPPLY AND ESTIMATION OF CRITICAL LIMITS FOR SUNFLOWER IN SOILS OF SUNFLOWER IN SOILS OF SUNFLOWER IN SOILS OF KUMAON REGION OF REGION OF UTTARAKHAND - GUPTA, SHILPI; D. K. SINGH, P. C. SRIVASTAVA AND (The Bioscan, 2016)
Twenty surface (0-15 cm) soil samples collected from different sites of Kumoun region of Uttarakhand (India) were analyzed for extractable soil B using five different soil extractants and soil test values were evaluated for predicting the response of B application in hybrid sunflower(Sankar Sunflower 6460).The soil extractants used in the study could be arranged in the following order of their B extraction capacity: Mehlich 3 (pH 2.0) > 0.01M CaCl2 + 0.05 M mannitol (pH 8.5) > 0.01 M CaCl2 > 0.05 M HCl>Hot water.Among soil extractants used in the study, B extractable in hot water, 0.05 M HCl and Mehlich-3 extractants correlated significantly with Bray’s per cent yield. The critical limits of B in soil were 0.27, 0.37 and 9.2 mg kg-1B extractable in hot-water, 0.05 M HCl and Mehlich-3 extractants. The critical limit of boron in hybrid sunflower plants was 27.4 mg B kg-1 dry plant tissue at 40 days after emergence. Calcium chloride+mannitol Critical limit Dilute hydrochloric acid method